2016
DOI: 10.7554/elife.11324
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-128 regulates the proliferation and neurogenesis of neural precursors by targeting PCM1 in the developing cortex

Abstract: During the development, tight regulation of the expansion of neural progenitor cells (NPCs) and their differentiation into neurons is crucial for normal cortical formation and function. In this study, we demonstrate that microRNA (miR)-128 regulates the proliferation and differentiation of NPCs by repressing pericentriolar material 1 (PCM1). Specifically, overexpression of miR-128 reduced NPC proliferation but promoted NPC differentiation into neurons both in vivo and in vitro. In contrast, the reduction of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 44 publications
0
54
0
Order By: Relevance
“…One recent report [140] shows that a microRNA, called miR-128, negatively regulates the cellular levels of PCM1. Overexpression of miR-128 resulted in downregulation of PCM1, leading to repressing proliferation of neural progenitor cells yet simultaneously promoting their differentiation into neurons.…”
Section: Neurogenesis and Pcm1mentioning
confidence: 99%
See 1 more Smart Citation
“…One recent report [140] shows that a microRNA, called miR-128, negatively regulates the cellular levels of PCM1. Overexpression of miR-128 resulted in downregulation of PCM1, leading to repressing proliferation of neural progenitor cells yet simultaneously promoting their differentiation into neurons.…”
Section: Neurogenesis and Pcm1mentioning
confidence: 99%
“…Overexpression of miR-128 resulted in downregulation of PCM1, leading to repressing proliferation of neural progenitor cells yet simultaneously promoting their differentiation into neurons. Conversely, the reduction of miR-128 elicited the opposite effects; promotion of proliferation and suppression of differentiation of neural progenitor cells [140]. Whether this inhibitory role of PCM1 in neurogenesis is exerted through centriolar satellite integrity is yet to be rigorously examined, but this would be a novel, intriguing aspect of the physiology of centriolar satellites.…”
Section: Neurogenesis and Pcm1mentioning
confidence: 99%
“…MicroRNAs (miRNAs) have emerged as important regulators of NPC proliferation and neocortex size [66][67][68][69][70][71][72].…”
Section: Micrornasmentioning
confidence: 99%
“…Furthermore, miR-128 has been shown to be downregulated in glioma, in which overexpressed miR-128 reduces neuroblastoma cell motility and invasiveness by inhibiting Reelin and DCX and inhibits cell proliferation by targeting E2F3a and Bmi-1 (apoptosisrelated genes) [28]. Overexpressed miR-128 suppresses the proliferation of neural progenitor cells while facilitating the differentiation of neural progenitor cells to neurons and regulates the neurogenesis of neural precursors by targeting PCM1 in the developing cortex [29]. In addition, Karam et al reported that miR-128 is induced in the differentiation of neuronal cells and during brain development, which contributes to the inhibition of nonsensemediated decay, and the regulation of mRNAs that encode proteins are strongly related to neuron differentiation and function [30].…”
Section: Discussionmentioning
confidence: 99%